Use of 3D Imaging in Planning Varus Derotation Osteotomy in Neuromuscular Hip Subluxation: Surgical/Technical Tips - Montgomery, Blake; Jarrett, Delma; Agahigian, Donna; Watkins, Colyn; Shore, Benjamin (Journal of the Pediatric Orthopaedic Society of North America, 2022)
Proximal femur varus derotation osteotomy (VDRO) is the primary component of hip reconstruction surgery for the management of hip subluxation/dislocation in patients with neuromuscular dysplasia. Understanding the pathophysiology and abnormal proximal femur geometry is crucial to performing a successful surgery and dosing the surgical correction accurately. Children with neuromuscular hip dysplasia experience increased coxa valga, femoral anteversion and variable degrees of acetabular dysplasia. Understanding the relationship between these three anatomic aberrations can be difficult with standard two-dimension plain radiography. In this paper, we will review our novel three-dimensional imaging protocol to assess the pathologic anatomy of the proximal femur and acetabulum in children undergoing neuromuscular hip reconstruction. Understanding the anatomic relationship between the neck shaft angle, anteversion and acetabular dysplasia aids in the planning and execution of effective VDRO and hip reconstruction surgery.